3p-6=10-2m

Simple and best practice solution for 3p-6=10-2m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p-6=10-2m equation:


Simplifying
3p + -6 = 10 + -2m

Reorder the terms:
-6 + 3p = 10 + -2m

Solving
-6 + 3p = 10 + -2m

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 3p = 10 + 6 + -2m

Combine like terms: -6 + 6 = 0
0 + 3p = 10 + 6 + -2m
3p = 10 + 6 + -2m

Combine like terms: 10 + 6 = 16
3p = 16 + -2m

Divide each side by '3'.
p = 5.333333333 + -0.6666666667m

Simplifying
p = 5.333333333 + -0.6666666667m

See similar equations:

| -12x-12=-11x+9 | | -4x=0.8 | | N/2-9=-9 | | -31+x=4x+20 | | -4+10+6x=28 | | -12+8x=6x+28 | | 3/6=g/90 | | 6n^2-45n+84=0 | | -5x-39=57+x | | -18p=-9 | | xx+1=0 | | 4lnx=60 | | -34+9x=6x+53 | | -4=-16x | | 7/8=n | | -29-10x=-12x+25 | | 37=5p-3 | | -152-x=8x+55 | | 10x+19=3x+229 | | 10x+19=3x+22 | | -82-12x=-5x+65 | | 48=4n+20 | | x+6=4x^2-12x+9 | | -101-3x=-10x+39 | | -95+12x=6x+31 | | Y^2=14y-48 | | =2x+2 | | -39+6x=10x+17 | | 47=5m+2 | | 14+1/5=10 | | 20(14-4)-4(6-4)= | | -20-3x=6-2x |

Equations solver categories